Participatory Varietal Evaluation of Rainy Season Tomato under Plastic House Condition - Pandey, YR; Pun, AB; Upadhyuy, KP (Nepal Agriculture Research Journal, 2009)
Four tomato varieties namely LTH-61, Avinash-2, NSITH-162 and BL-410 were evaluated infarmer's field with farmers participation under plastic house condition for yield potential andother yield characters at Hemja, Kaski (920 masl) during rainy seasons of two consecutive years2002 and 2003. The experiment was arranged in randomized complete block design with 5replications, farmer as a replication. NSITH-162 took the shortest period of days to floweringand first harvest with an average of 36 and 66 days after transplanting respectively. Fruit setafter flowering was highest in NSITH-162 (93.9%) and the lowest in Avinash-2 (83.1%).NSITH-162 produced the highest marketable fruit yield (89.05 t/ha) and Avinash-2 produced thelowest (51.98 t/ha). The results of the experiment revealed that the hybrid varieties NSITH-162and LTH-61 have more yield potentiality than open pollinated variety BL-410 and Avinash-2 anIndian hybrid variety and therefore NSITH-162 variety could be recommended for commercialproduction under plastic house condition.Key words: Participatory; plastic house; rainy season; tomatoDOI: 10.3126/narj.v7i0.1860Nepal Agriculture Research Journal Vol.7 2006 pp.11-15